WEAR BEHAVIOUR AND ITS CORRELATION TO RESIDUAL STRESSES FOR NICKEL HARD IRONS (Journal of Manufacturing Engineering, 2017)
The material, Nickel- Chromium, is extensively used for wear resistant applications in thermal power stations, mining, earth moving applications and other engineering industries. While the erosion and abrasion behavior are known in respect of Nickel-hard under various test conditions, the residual stress levels arising due to varied processing conditions, like heat treatment, cooling rate etc, needs to be investigated as the literature on this is scanty. These aspects have been addressed in the present work by linking wear and residual stresses of materials. The experimental results show that the residual stress levels as well as wear properties get affected due to varied cooling rates employed during casting process. The heat treatment of the castings has brought about significant change in the stress levels as well as erosion and abrasion behavior. The structural aspects linking wear and residual stresses in Ni-hard have also been brought out. Thus, a good correlation between wear (erosion and abrasion) and residual stresses has been established.
Keywords: Ni-Cr irons; abrasion; wear; retained austenite; residual stresses